2012
DOI: 10.1021/mz300032w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Rod-Like Dendronized Polymers Containing G4 and G5 Ester Dendrons via Macromonomer Approach by Living ROMP

Abstract: High generation dendronized polymers with high molecular weight were synthesized by ROMP via macromonomer approach. The polymerization was achieved in living manner and the macromolecules exhibited rod-like conformation. Correlation between the monomer structures and the conformation of the final polymers was investigated in detail. The rigid rod conformation in solution was confirmed by both light scattering and viscometric analysis and the single polymer chains were visualized by AFM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 49 publications
(25 reference statements)
1
57
0
Order By: Relevance
“…Once pseudo-ortho isomers shall be polymerized, harsh conditions become necessary and thus the high stability of HG2 catalyst (4) becomes mandatory. 36 In order to prove the quality of catalyst 6, two polymers with higher DPs were synthesized. High molecular weight polymers are accessible only by using isomers 2a and 2b (only short polymers are obtained when isomer 2c is used).…”
Section: Resultsmentioning
confidence: 99%
“…Once pseudo-ortho isomers shall be polymerized, harsh conditions become necessary and thus the high stability of HG2 catalyst (4) becomes mandatory. 36 In order to prove the quality of catalyst 6, two polymers with higher DPs were synthesized. High molecular weight polymers are accessible only by using isomers 2a and 2b (only short polymers are obtained when isomer 2c is used).…”
Section: Resultsmentioning
confidence: 99%
“…This result could be explained by a lower thermal stability of G3 and G3′ compared to G2 and HG2. 35 The polymers obtained using G2, G3, and G3′ displayed low dispersity values (Đ M ≤ 1.16) ( Figure 5A). When HG2 initiator was used, the SEC traces of the resulting polymers showed a shoulder toward higher molecular weights ( Figure 5E), which is consistent with a higher concentration of active species as explained previously.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Having demonstrated that the G1 functional dendron monomers are susceptible to homopolymerization with Grubbs' I and III initiators, albeit with relatively low Xtrue‾ n , we next evaluated the ability to prepare homopolymers with significantly higher Xtrue‾ n . For this series of experiments we focused exclusively on the bis pyrrole and protected sugar derivatives employing the Grubbs' III initiator with polymerizations performed in THF at 50 °C . Table gives a summary of the theoretical targeted Mtrue‾ n values, together with the target Xtrue‾ n values at quantitative conversion and the SEC measured number‐ and weight‐average molecular weights and Đ M values.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, and in the context of the work reported here, it has been demonstrated previously that metathesis polymerizations are suitable techniques for the preparation of dendronized (co)polymers via the macromonomer approach . For example, Rajaram et al reported the synthesis of AB diblock copolymers based on aryl ether dendron exo ‐norbornene macromonomers via ROMP with the Grubbs' III catalyst, RuCl 2 (3‐BrPy) 2 (ImMesH 2 )CHPh, to give materials of high‐number average molecular weight ( M n ) and low dispersity, as determined by multi‐angle laser light scattering.…”
Section: Introductionmentioning
confidence: 85%